Catalogue of artefacts from Malta in the British Museum - Briffa, Josef Mario, (Archaeopress archaeology., 2017)
Ancient finds from the Maltese islands are rare, and those held in the British Museum form an important collection. Represented is a wide cultural range, spanning the Early and Late Neolithic, the Bronze Age, Roman and more recent historic periods.